2019
DOI: 10.1159/000501589
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Exercise Training and Nontraditional Cardiovascular Risk Factors in Hemodialysis Patients: Results from a Prospective Randomized Trial

Abstract: Introduction: Chronic kidney disease (CKD) patients have a high incidence of cardiovascular diseases (CVD) which increases their morbidity and mortality. A sedentary lifestyle in CKD is directly linked to the onset of CVD. Physical activity can bring beneficial effects to CKD patients. Aims: The aim of this study was assess the impact of aerobic training on nontraditional cardiovascular risk factors in CKD patients on hemodialysis. Materials and Methods: This is a prospective, controlled, and randomized clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…In total, six studies (total n5315) examined outcomes related to myocardial structure (Table 4). 32,53,55,60,64,66 4B). 53,60,64,66 Cardiac Autonomic Dysfunction/Increased Sympathetic Activity Four RCTs (total n5205) assessed the effect of intradialytic cycling for 30-90 minutes, thrice weekly over 12-52 weeks of duration on various measures of HRV (Table 4).…”
Section: Myocardial Structurementioning
confidence: 99%
See 2 more Smart Citations
“…In total, six studies (total n5315) examined outcomes related to myocardial structure (Table 4). 32,53,55,60,64,66 4B). 53,60,64,66 Cardiac Autonomic Dysfunction/Increased Sympathetic Activity Four RCTs (total n5205) assessed the effect of intradialytic cycling for 30-90 minutes, thrice weekly over 12-52 weeks of duration on various measures of HRV (Table 4).…”
Section: Myocardial Structurementioning
confidence: 99%
“…32,53,55,60,64,66 4B). 53,60,64,66 Cardiac Autonomic Dysfunction/Increased Sympathetic Activity Four RCTs (total n5205) assessed the effect of intradialytic cycling for 30-90 minutes, thrice weekly over 12-52 weeks of duration on various measures of HRV (Table 4). 49,53,60,68 Meta-analysis of these studies showed no statistically significant difference in the SD of normal R-R intervals during a 24-hour period (SD of N-N intervals [SDNN]) in the exercise group as compared with the control group (MD 16.05 ms; 95% CI, 214.60 to 46.70; I 2 599%; P , 0.001).…”
Section: Myocardial Structurementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its independent effects on traditional CVD risk factors, regular physical activity can also improve cardiovascular health and impact upon nontraditional or novel CVD risk factors, such as C-reactive protein and oxidative stress [21,22]. Physical activities' effectiveness at preventing and managing CVD is due to its ability to target various pathways through which it influences different physiological systems, such as its ability to promote a healthy anti-inflammatory environment, largely through the release of muscle-derived myokines, its ability to stimulate myocardial regeneration and its ability to improve age-related loss of muscle mass and strength, a frequently overlooked non-traditional CVD risk factor [23][24][25].…”
Section: Physical Activity and Cvdmentioning
confidence: 99%
“…Endothelial dysfunction appears in the early stages of CKD 28 and can be evaluated noninvasively by flow mediated vasodilation (fmv), which is an important predictor of coronary events in patients with CKD, further increasing the correlation between endothelial dysfunction and CVD risk 38 . It can be attributed to intrinsic microenvironment's alterations observed in CKD such as high aldosterone levels 39 , subclinical inflammation 39 , excessive oxidative stress, and NO dysregulation 3 , as well as defective endothelial repair mechanisms due to reduced levels of bone marrowderived endothelial progenitor cells and impaired migratory function of circulating angiogenic cells 40 . Unfortunately there are only two trials meeting our inclusion criteria.…”
Section: Vascular Dysfunctionmentioning
confidence: 99%